Actoprotective activity of 5-(2-bromophenyl)-4-amino-4H-1,2,4-triazole-3-thione and its S-derivatives - Ye. S. Pruglo (Zaporozhye State Medical University, 2016)
Aim. The paper shows the actoprotective (anti-fatigue), activity of 1,2,4-triazole derivatives. Methods and results. The analysis of action was conducted for the synthesized 2-(5-(2-bromphenyl)-4-amino-4H-1,2,4-triazol-3-ylthio) acetic acid salts. We have revealed some patterns regarding to the chemical structure and pharmacological action of the test substances. Thus, in the research we have found that the most active compound among the studied was morpholinium 2-(5-(2-bromphenyl)-4-amino-4H-1,2,4-triazol-3-ylthio) acetate (3j), which increases the duration of rats (forced swimming with the load) as compared with the control group at 77,17% (p˂0,05), while the reference drug increases the rate at 24,16% (p˂0,05). We have noted the compound 3i which exceed its activity comparing to Riboxinum at 23,2%, with increased endurance during the animals forced swimming test to 47,36% (p˂0,05). Conclusions. It is marked that the parent thione 1a and its derivative of 2-(5-(2-bromophenyl)-4-amino-4H-1,2,4-triazol-3-ylthio) acetic acid salt 2a and 3d, 3e, 3f have no actoprotective properties in their application. After analyzing the data of experimental studies some laws concerning the chemical structure and pharmacological action of the test substance have been established.